Role of Renewable Energy, Economic Growth, Agricultural Productivity, and Urbanization Toward Achieving China’s Goal of Net-zero Emissions - Rahman, Md. Shoaibur; Ridwan, Mohammad; Raihan, Asif; Khayruzzaman; Tanchangya, Tipon; Rahman, Junaid; Foisal, Md. Zia Uddin; Mohajan, Babla; Islam, Samanta; Rafi, Azizul Hakim; Paul, Arindrajit; Ahmad, Shakil (Journal of Environmental and Energy Economics, 2023)
An increase in carbon dioxide (CO2) is expected to raise the Earth's temperature, leading to consequences such as glacier melt, rising sea levels, changes in weather patterns, and increased frequency of droughts and hurricanes. To restrict global warming to a maximum of 1.5°C, as outlined in the Paris Agreement, emissions must be reduced by 43% by 2030 and reach net zero by 2050. This investigation thoroughly examines the relationship between GDP growth, agricultural production, renewable energy use, urbanization, and CO2 emissions in China from 1965 to 2023. Employing complex econometric models, such as Autoregressive Distributed Lag (ARDL), the research delivers a thorough analysis. The results indicate a substantial inverse connection between agricultural productivity and CO2 releases, highlighting the efficacy of organic farming practices for ecological protection. Economic growth, despite its statistically small effect on pollution, highlights the necessity for ecologically sound and technologically sophisticated enhancement plans. The research underscores the significance of green power adoption in reducing CO2 emissions in China in accordance with international initiatives for ecologically friendly production. The strong association between urbanization and CO2 emissions implies difficulties in reconciling urban expansion with protecting the ecosystem. The study provides important guidance for formulating specialized green initiatives in China, aiding the country's goal of achieving net-zero emissions by 2060. The report offers a framework for healthy development, highlighting the benefits of farming and clean energy while tackling the challenges posed by urbanization, as China's experiences parallel those of other rising nations. This thorough research enhances the worldwide dialogue on addressing global warming and promoting responsible growth.